2012
DOI: 10.4137/ccrep.s9318
|View full text |Cite
|
Sign up to set email alerts
|

Human Rabies with Initial Manifestations that Mimic Acute Brachial Neuritis and Guillain-Barré Syndrome

Abstract: IntroductionHuman rabies can be overlooked in places where this disease is now rare. Its diagnosis is further confused by a negative history of exposure (cryptogenic rabies), by a Guillain-Barré syndrome (GBS) type of presentation, or by symptoms indicating another diagnosis, eg, acute brachial neuritis (ABN).Case presentationA 19-year-old Mexican, with no past health problems, presented with a two-day history of left shoulder, arm, and chest pain. He arrived in Louisiana from Mexico five days prior to admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The vast majority (85.0%) of cases resulted from exposure to dogs. Three cases resulted from bat-related injuries, including one case of a Dutch tourist returning from Kenya [3]–[5], one case of a US citizen injured in the US who developed rabies symptoms while expatriated in Iraq and was subsequently evacuated to Switzerland [6], and one case of a Mexican citizen who developed rabies in the US where he was involved in seasonal work [7], [8]. One case was observed in Russia following a fox bite that occurred in Ukraine [2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority (85.0%) of cases resulted from exposure to dogs. Three cases resulted from bat-related injuries, including one case of a Dutch tourist returning from Kenya [3]–[5], one case of a US citizen injured in the US who developed rabies symptoms while expatriated in Iraq and was subsequently evacuated to Switzerland [6], and one case of a Mexican citizen who developed rabies in the US where he was involved in seasonal work [7], [8]. One case was observed in Russia following a fox bite that occurred in Ukraine [2].…”
Section: Resultsmentioning
confidence: 99%
“…A 50-year-old French female tourist sustained multiple deep dog bites on the legs during a trip in India and developed rabies 12 days later while returning to France [9], [10]. A 19-year-old male Mexican seasonal worker was bitten by a bat on his leg and developed rabies due to a variant virus of vampire bat rabies 15 days later in the US [7], [8]. In three cases, very long incubation times were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially in the case presented here, the chief complaint of chest pain deviated the medical team's attention/focus away from a diagnosis of rabies to heart disease. Though uncommon, such cases have been reported ( Table 2) [4][5][6][7][8] , since rabies can caused focal interstitial myocarditis as discussed by Park et al 9 In the case series reported by Mani et al 10 , all cases presented without evidence of chest pain, so the clinical presentations of rabies vary. Furthermore, concerning the classical sign of fear of water, in our case, the patient 11 In terms of the forensics aspect, since a rabies investigation is not performed on every case with an unknown cause of death examined by only external examination, the forensic physician thought of rabies infection as the cause of death based on the review of the history recorded on the first emergency room visit and the numerous dogs observed by the forensic physician at the crime scene during the post-mortem visit at the patients residence.…”
Section: Discussionmentioning
confidence: 99%